The Value of Cognitive Pretesting: Improving Validity and Revealing Blind Spots through the Development of a Newborn Screening Parent Experiences Survey - Norma-Jean Simon; Anne Atkins; Brianne Miller; Natasha Bonhomme; Beth Tarini (MDPI AG, 2021)
Surveys are used to gather a range of data on newborn screening (NBS) processes. We describe the development of a survey about parents' NBS experiences, in the United States, informed by cognitive pretest interviews among parents with varying NBS test results (true-positive, false-positive, normal). Cognitive pretest interviews were conducted following a semi-structured script and notes were taken to identify problematic survey items. The study team met weekly to discuss pretest feedback, draft changes, and generate revised items. Pretests indicated that parent experiences with NBS are varied and NBS screening procedures are not well understood. Substantial modifications were made to survey questions concerning NBS testing and result communication. Pretesters often associated NBS with other tests/exams/scales-APGAR scores, Ages and Stages questionnaires, and genetic testing during pregnancy. Some pretesters recalled receiving NBS blood spot results during their hospital admission, an uncommon practice, and few recalled knowing results would be provided to them or their pediatrician in the first few weeks of life. Thorough explanations regarding NBS procedures and expectations were embedded within the survey to enhance and improve interpretation of survey questions. Future NBS experience surveys should utilize cognitive pretesting to capture divergent experiences and improve response validity.